2014
DOI: 10.1590/1678-476620141044426431
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomic status of Phlebotomus oliverioi (Diptera, Psychodidae) and a lectotype designation for Psathyromyia brasiliensis

Abstract: ABSTRACT. Phlebotomus oliverioi Barretto & Coutinho, 1941 was originally described based only on the male holotype and has since been considered junior-synonym of Psathyromyia brasiliensis (Costa Lima, 1932). The study of the holotype of Ph. oliverioi allowed us to conclude that the head of this specimen belongs to the genus Psychodopygus and the wings, thorax and abdomen belong to a different species of Psathyromyia. Thus, Ph. oliverioi is a not valid species, and must be removed from the synonym and excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Note. Andrade et al (2014) examined the holotype and concluded that the head of this specimen belongs to a specimen of Psychodopygus while the wings, thorax and abdomen belong to another specimen, of the genus Psathyromyia .…”
Section: Systematicsmentioning
confidence: 99%
“…Note. Andrade et al (2014) examined the holotype and concluded that the head of this specimen belongs to a specimen of Psychodopygus while the wings, thorax and abdomen belong to another specimen, of the genus Psathyromyia .…”
Section: Systematicsmentioning
confidence: 99%
“…Entomological repositories and collections are essential for the study of insect taxonomy and systematics, above all those of medical interest, since it is possible to consult the material and compare it with the original description to check the taxonomic status of the species, for example (Andrade et al, 2013(Andrade et al, , 2014. A consultation of type material already collected and catalogued becomes an interesting alternative for the study of vectors, since there is information on taxonomic aspects, taxonomic status of the specimen and the biogeography of a specimen or group, principally of those groups that are difficult to capture (Cranston, 2005).…”
Section: Discussionmentioning
confidence: 99%